Asymmetric Lewis Acid Catalyzed Electrochemical Alkylation. Issue 21 (10th April 2019) - Zhang, Qinglin; Chang, Xihao; Peng, Lingzi; Guo, Chang
Abstract: Lewis‐acid catalysis and electrochemistry represent two powerful fields that have found widespread application in organic chemistry. Reported herein is an asymmetric electrosynthesis in combination with a chiral Ni catalyst leading to an intermolecular alkylation reaction in good yields with excellent enantioselectivities (up to 97 % ee ). Mechanistic studies suggest that the Lewis‐acid‐bound radical intermediate from a single‐electron anodic oxidation selectively reacts with the benzylic radical species to generate the desired adducts. Abstract : Electrifying : An efficient asymmetric electrosynthesis was developed with high yields and excellent enantioselectivities by using a chiral Ni catalyst. Mechanistic studies suggest that the Lewis‐acid‐bound radical intermediate, from a single‐electron anodic oxidation, selectively reacts with a benzylic radical species to generate the desired adducts.